1998
DOI: 10.1094/mpmi.1998.11.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of Two Phosphate Transporters from Medicago truncatula Roots: Regulation in Response to Phosphate and to Colonization by Arbuscular Mycorrhizal (AM) Fungi

Abstract: Most vascular plants can acquire phosphate from the environment either directly, via the roots, or indirectly, via a fungal symbiont that invades the cortical cells of the root. Here we have identified two cDNA clones (MtPT1 and MtPT2) encoding phosphate transporters from a mycorrhizal root cDNA library (Medicago truncatula/Glomus versiforme). The cDNAs represent M. truncatula genes and the encoded proteins share identity with high-affinity phosphate transporters from Arabidopsis, potato, yeast, Neurospora cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
212
1
10

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 267 publications
(234 citation statements)
references
References 49 publications
11
212
1
10
Order By: Relevance
“…Means followed by the same letter within columns are not significantly different by Duncan's multiple range test at the 5% level. downregulate high-affinity phosphate transporters (MtPT1 and MtPT2) which may be responsible for absorption of phosphate from soil by M. truncatula (Liu et al, 1998;Chiou et al, 2001;Burleigh, 2001). Furthermore, studies on the kinetics of phosphate/arsenate uptake have suggested that AMF can downregulate phosphate/arsenate transporters in both arsenate resistant and non-resistant Holcus lanatus (Gonzalez-Chavez et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Means followed by the same letter within columns are not significantly different by Duncan's multiple range test at the 5% level. downregulate high-affinity phosphate transporters (MtPT1 and MtPT2) which may be responsible for absorption of phosphate from soil by M. truncatula (Liu et al, 1998;Chiou et al, 2001;Burleigh, 2001). Furthermore, studies on the kinetics of phosphate/arsenate uptake have suggested that AMF can downregulate phosphate/arsenate transporters in both arsenate resistant and non-resistant Holcus lanatus (Gonzalez-Chavez et al, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…To sort out these complications requires more detailed investigations of growth parameters and P uptake patterns for both roots and AMF in compartmented systems, beyond the scope of the present study. Such investigations will also help in determining the extent to which P uptake via AMF results in changes of expression of P transporter genes in roots (see Liu et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Plant material and growth conditions M. truncatula was grown under conditions with varying levels of phosphate as described previously (Liu et al, 1998b). Brie¯y, 10-day-old seedlings were grown on acid washed, sterilized river sand and fertilised with half-strength Hoagland's solution containing either 0, 0.02, 0.1, 1.0, or 5.0 mM KH 2 PO 4 three times a week.…”
Section: Methodsmentioning
confidence: 99%
“…The RNA was separated on a formaldehye gel, blotted and hybridised with either 32 P-labeled MtPT1 cDNA or 32 P-labeled MtPT1 oligo (Liu et al, 1998b).…”
Section: Northern Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation